2015
DOI: 10.1088/0004-637x/814/1/32
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of an Asymmetric Debris Disk in the Hd 106906 Planetary System

Abstract: We present the first scattered light detections of the HD 106906 debris disk using Gemini/GPI in the infrared and HST/ACS in the optical. HD 106906 is a 13 Myr old F5V star in the Sco-Cen association, with a previously detected planet-mass candidate HD 106906b projected 650 AU from the host star. Our observations reveal a near edge-on debris disk that has a central cleared region with radius ∼50 AU, and an outer extent >500 AU. The HST data show the outer regions are highly asymmetric, resembling the "needle" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 64 publications
4
106
0
Order By: Relevance
“…The inner disk has little to no vertical extension. While Kalas et al (2015) tentatively suggested the presence of a "warp" in the disk's vertical structure on the west side of the disk, this warp was not confirmed by Lagrange et al (2016). This lack of vertical extension indicates that the inclinations of the disk particles have not been excited.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The inner disk has little to no vertical extension. While Kalas et al (2015) tentatively suggested the presence of a "warp" in the disk's vertical structure on the west side of the disk, this warp was not confirmed by Lagrange et al (2016). This lack of vertical extension indicates that the inclinations of the disk particles have not been excited.…”
Section: Introductionmentioning
confidence: 86%
“…4. Kalas et al (2015) observed a faint extension on the west side of the disk out to nearly 500 au, but only diffuse emission on the east side.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations